Pemikiran Ekonomi Islam Seputar Sharf Menurut Taqiyuddin Al-nabani - Ja'far Nasution (Institut Agama Islam Negeri Padangsidimpuan, 2016)
The money be acquainted with a certain term by human is getting that goods have value.And as wages for merit and service.Whether have a shape a metal or not. The goods,labors and services are obtaining values with money.Whose name is Taqiyuddin bin Abu Ibrahim Taqiyuddin Muhammad bin Ibrahim bin Mushthofa bin Ismail bin Yusuf bin Hasan bin Muhammad bin Nashiruddin an-Nabhani born in Ijzim 1909.He was a prominent figure, brainware and politican at 20 century.Exchange currency with other currency of kind is signing equal heavy and kind absolutely not overdo one on another.The reason this action included riba and verdict haram.Like change gold and gold, included change currency who value can change with gold with gold, cause this kind is not be valid a rate of exchange.It so happens exchange currency with another currency is difference kind it, like exchange gold with silver, pounsterling with dollar, rubel with franc, follow laws is neutral set as condition collective hand over on the location. The calculation one for other it is name rate of exchange. So, the rate exchange is the calculation exchange between two currency difference.